12 Locally Intermediate Glottic Cancer: Vertical Partial Laryngectomy (Laryngeal Cancer, 2019)
Radiotherapy, laser endoscopic excision, and partial laryngectomy are the options in the treatment and of the moderate-stage cancer of the larynx. The decision must consider the patient’s expectations. For the case described here, vertical technique (hemilaryngectomy) and the horizontal technique (horizontal supracricoid laryngectomy) may be recommended. The main advantage of the hemilaryngectomy is the maintenance of the hemilarynx structures not involved by the carcinoma. Probably the cases presenting microscopic infiltration of the thyroid cartilage for cancer would be eligible for transoral laser resection. Vertical laryngectomies are still a good option in cases where endoscopic surgery does not suffice or when it is not available, such as in some developing countries. The need for the reconstruction of the endolarynx by using flaps and grafts allows for a better glottic coaptation. The oncologic outcome is less favorable in cancer extending beyond the confines of the vocal folds, in which supracricoid laryngectomy can be performed.
Keywords: laryngectomy; laryngeal cancer; carcinoma; squamous cell; reconstructive techniques; voice